الصلة بين المنهج الفلسفي والبحث العلمي (Comprehensive Journal of Science, 2025)
Science is a civilizational phenomenon, and scientists in their various specializations have made great efforts to complete this phenomenon and benefit from it in scientific and practical life until science has become an effective contributor to the cognitive construction of man and the formation of his mind, and changing his reality, and it has become The history of science is the history of science and its interaction with empirical experiences or the indications of the senses. It is an original document between philosophy and science that confirms the inevitability of a close relationship between science and philosophy. We can understand this interest in the philosophical aspect of science by those with experience. Creative and imaginative minds, if we remember that fundamental changes in science have always been accompanied by a deeper exploration of philosophical foundations. All these considerations make it clear that anyone seeking an acceptable understanding of twentieth-century science must have a substantial grasp of philosophical thought. Hence, a study of the history of science and philosophical thought is essential to scientific and philosophical research. It inevitably reveals many connections between them, to the point of intimacy, as they both seek the truth. Therefore, the philosophy of science has become inseparable from the historical dimensions of the phenomenon of science, and has become deeply concerned with the history of science. The philosophical approach provides the theoretical foundations upon which scientific research relies and helps philosophers explore concepts such as truth, knowledge, and existence, guiding scientists in formulating their own ideas. Their hypotheses. Philosophy also encourages the asking of profound questions about the topics under investigation. These questions lead to new scientific explorations and expanded research. The philosophical approach enhances critical thinking, helping researchers better evaluate evidence and interpret results. This analysis is essential to ensure the reliability of results. Philosophy plays a role in the development of many scientific theories based on philosophical principles, which enhances Their hypotheses. Philosophy also encourages the asking of profound questions about the topics under investigation. These questions lead to new scientific explorations and expanded research. The philosophical approach enhances critical thinking, helping researchers better evaluate evidence and interpret results. This analysis is essential to ensure the reliability of results. Philosophy plays a role in the development of many scientific theories based on philosophical principles, which enhances From our understanding of natural phenomena. There is also an ongoing interaction between philosophy and scientific research. Philosophers are inspired by scientific discoveries, while philosophy helps direct scientific research toward new questions. The philosophical method and scientific research are closely linked, with each contributing to the enhancement of the other. Philosophy provides a theoretical framework that helps understand and explain Scientific data, while scientific research provides philosophy with material for analysis and criticism, and thus philosophy and the scientific methods it created throughout its long history were the basis for opening up the horizons of science with scientific knowledge, and thus knowledge was split until science itself began to produce philosophy.